STRATEGI MARKETING MIX JASA PENDIDIKAN DALAM MENUMBUHKAN ANIMO CALON PESERTA DIDIK MEMILIH SEKOLAH - Firman Budi Santoso; Asep Sunandar; Ahmad Nurabadi; Ahmad Yusuf Sobri; Firman Budi Santoso; Asep Sunandar; Ahmad Nurabadi (Universitas Negeri Malang, 2024)
Abstract: This study aims to describe (1) the marketing mix aspects of educational services;(2) marketing mix strategy of educational services; and (3) the implications of theeducational services marketing mix strategy. The method used is a qualitativeapproach with the type of case study research at SMK Muhammadiyah 2 Malang.Data were collected using interview, observation, and documentation techniques.The results of this study show(1) aspects of the educational service marketing mixcovering aspects of price, product, location, promotion, people, process, andphysical evidence in the form of school excellence; (2) The education servicemarketing strategy starts from determining segmentation, targeting, andpositioning as a determinant of the agency's marketing direction, then managingaspects of the marketing mix into a content and promotion strategy in accordancewith community needs and institutional needs; (3) strategic implications arise inevery aspect of the marketing mix in the form of the development of studentinterest and institutional cooperation.